2014
DOI: 10.1210/en.2014-1465
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Effect of In Vitro Fertilization (IVF) on Adult Mouse Fat and Liver Metabolomes

Abstract: The preimplantation embryo is particularly vulnerable to environmental perturbation, such that nutritional and in vitro stresses restricted exclusively to this stage may alter growth and affect long-term metabolic health. This is particularly relevant to the over 5 million children conceived by in vitro fertilization (IVF). We previously reported that even optimized IVF conditions reprogram mouse postnatal growth, fat deposition, and glucose homeostasis in a sexually dimorphic fashion. To more clearly interrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 47 publications
13
39
0
Order By: Relevance
“…The increased ratio of placental/fetal weight observed in this study is similar to that described in human IVF pregnancies, where IVF offspring were associated with hypertension later in life (Barker et al 1990, Moore et al 1996, Koudstaal et al 2000. The reasons for the increased ratio of placental/fetal weight are likely complicated; one possible explanation involves a compensatory process for the depressed fetal growth or the impaired function of the placenta itself (Feuer et al 2014, Chen et al 2015. The placental/fetal weight ratio was higher for IVF males than IVF females.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The increased ratio of placental/fetal weight observed in this study is similar to that described in human IVF pregnancies, where IVF offspring were associated with hypertension later in life (Barker et al 1990, Moore et al 1996, Koudstaal et al 2000. The reasons for the increased ratio of placental/fetal weight are likely complicated; one possible explanation involves a compensatory process for the depressed fetal growth or the impaired function of the placenta itself (Feuer et al 2014, Chen et al 2015. The placental/fetal weight ratio was higher for IVF males than IVF females.…”
Section: Discussionsupporting
confidence: 82%
“…For example, IVF is associated with higher risks of female-biased Rett syndrome (Arnaud & Feil 2005) and male-biased Autism (Fountain et al 2015), and some IVF-associated birth defects show sexually dimorphic patterns (Michalski et al 2015). Furthermore, sex-specific effects of IVF on postnatal metabolism and growth of IVF-conceived offspring has been confirmed in mouse models (Scott et al 2010, Feuer et al 2014). More importantly, recent studies indicate that IVF results in a skewed sex ratio at birth (Dean et al 2010, Bu et al 2014, Maalouf et al 2014, reflecting sex-biased or even specific disruption of embryonic development.…”
Section: Introductionmentioning
confidence: 88%
“…In mice, long-term effects associated with in vitro fertilization (IVF), intracytoplasmic sperm injection (ICSI) and somatic cell nuclear transfer (SCNT) were found to be sex specific, with females showing altered glucose clearance, higher body weight and adiposity (Scott et al 2010a). In agreement, another study reported sex-specific differences in sterol metabolism, redox state, mobilization and oxidation of fatty acids after IVF in murine offspring, with females being more predisposed to increased fat accumulation (Feuer et al 2014).…”
Section: Sex-specific Long-term Effects Mediated By Assisted Reproducsupporting
confidence: 73%
“…However, in another study in mice produced from IVF, altered postnatal growth and glucose intolerance were only observed in males (Donjacour et al 2014). Additional sexual dimorphic patterns induced by IVF were reported by Tan and coworkers (Tan et al 2016).…”
Section: Sex-specific Long-term Effects Mediated By Assisted Reproducmentioning
confidence: 60%
“…They expressed pluripotent markers and had a capacity to generate derivatives representative of all three germ layers in vivo and in vitro. Recently, many groups reported that IVF altered gene methylation mode and metabolic physiology (Feuer et al 2014;Hiura et al 2014;Nelissen et al 2014). This alteration may be arose early in embryogenesis.…”
Section: Resultsmentioning
confidence: 99%